2013
DOI: 10.1016/j.neuroscience.2012.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of axo-spinous synapses in the pathophysiology and treatment of depression

Abstract: Dendritic spines provide a compartment for assembly and functional organization of synaptic machinery that plays a fundamental role in neuronal communication and neuroplasticity. Studies in humans as well as in animal models have demonstrated abnormal spine architecture in several psychiatric disorders, including depression and other stress related illnesses. The negative impact of stress on the density and organization of spines is thought to contribute to the behavioral deficits caused by stress exposure. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 253 publications
(289 reference statements)
3
89
0
Order By: Relevance
“…Concomitantly, both dendrite shrinkage and spine loss were induced by restraint stress in the hippocampus, whereas dendrite growth and increase of spine density were induced in the basolateral amygdala [29,30]. These contrasting structural changes were also reported in the hippocampus and amygdala of patients suffering from major depressive and anxiety disorders [31,32]. The present study showed that hypergravity down-regulated the expression of BNDF mRNA in the ventral hippocampus but had no effect in the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, both dendrite shrinkage and spine loss were induced by restraint stress in the hippocampus, whereas dendrite growth and increase of spine density were induced in the basolateral amygdala [29,30]. These contrasting structural changes were also reported in the hippocampus and amygdala of patients suffering from major depressive and anxiety disorders [31,32]. The present study showed that hypergravity down-regulated the expression of BNDF mRNA in the ventral hippocampus but had no effect in the amygdala.…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen influences neurotransmitter activity, neurogenesis, and neurotrophic factor expression, as well as many aspects of glial function 58,61,62 . Notably, BDNF levels fluctuate with the estrous cycle and estrogen administration can increase the expression of BDNF in the PFC and hippocampus 6366 .…”
Section: Sex Differences In Susceptibility To Depressionmentioning
confidence: 99%
“…There is evidence of vmPFC gray matter loss in mood disorders 7,115,116 , which implies dendritic atrophy. However, there have been no direct studies of changes in spine numbers in these circuits.…”
Section: Potential Relevance To Spine Loss In Mental Disordersmentioning
confidence: 99%